Portable real time microwave milk quality monitoring sensor - Iram, Lubina; Sandhu, Muhammad Y.; Hossain, A.K.M Zakir; Khan, Sanaullah (2023)
This work presents the design of a handheld real time microwave sensor and set-up for the monitoring of milk quality. A single pole co-axial cavity bandpass resonator is used as a microwave sensor. A rectangular hollow Acrylonitrile butadiene styrene ABS sample holder is placed inside the resonator for characterizing loaded milk samples. A sensor is designed to detect adulteration in milk samples by measuring the amount of energy coupled between input and output ports. It is validated using both lab-based and low-cost portable setups. The sensor is capable of accurately detecting the level of adulteration in milk samples in batch and continuous modes of operation. The measured results demonstrate the capability of the designed sensor to detect the level of adulteration of milk with various percentages of water, urea, and detergent contamination in real-time. This design would motivate the RF and Microwave sensor designers to produce a well efficient and durable milk quality monitoring sensor for the food industry.